Influência do meio hiperglicêmico intrauterino em diferentes fases de vida dos descendentes de ratas - Iessi, Isabela Lovizuto [UNESP] (2012)
We hypothesized that not only insulin is relevant for embryofetal development and diabetes-derived alterations as well the glucoregulatory hormones glucagon and somatostatin. To investigate this possibility in rat pregnancy and in their offspring, we have compared glycemia, insulin, glucagon and somatostatin in late pregnancy and postnatal period to associate with maternal reproductive outcomes of diabetic rats. Wistar rats were randomly assigned into: Non diabetic (C); Mild diabetes (MD); and Severe diabetes (SD). Diabetes was induced in rats by streptozotocin. The female rats were mated and two experiments to evaluate pancreatic hormone were conducted: death of dams and their respective fetuses at day 21 of pregnancy and at day 10 postpartum (newborn assessment). The SD and MD rats presented impaired reproductive performance. In general, the rats presenting severe diabetes and their offspring showed metabolic desarrangement confirmed by reduced body weight and alterations in the pancreatic hormone levels. In the presence of mild diabetes, the offspring presented similar metabolic response to those of their dams against maternal hyperglycemic insult. The diabetes decreased embryofetal competence and caused alterations in the glucoregulatory hormones (glucagon and somatostatin), which showed that somatostatin might be the hormone more susceptible to these changes. This study demonstrates the importance in studying glucagon and somatostatin more profoundly, because of these hormones could be predictor factors of the adverse results in the adult life